Marketing Improvement Strategy For Laku Pandai Agents At Bank Kalteng, Pangkalan Bun Branch (Pusat Riset dan Inovasi Nasional, 2026)
The development of digitalization has contributed to progress in Indonesia’s banking sector, making banking services more flexible and widely accessible to a society with increasingly dynamic needs. A 2021 survey conducted by the Secretariat of the National Council for Financial Inclusion (S-DNKI) showed that 83.60% of adults had recognized and used financial products and services. Despite the growth of agents and bank account ownership, challenges arise regarding the readiness of Laku Pandai agents in marketing available products due to suboptimal understanding and use of digital tools, as well as limited marketing capabilities. Therefore, effective marketing strategies for Laku Pandai agents are needed to generate maximum impact, such as expanding agent outreach to better reach communities in various regions. This study employs a library research method, which involves collecting existing literature, followed by reading, recording, and processing the data. The research was conducted on Laku Pandai agents partnered with the Regional Development Bank of Central Kalimantan, Pangkalan Bun Branch. The conclusion of this study, titled “Marketing Strategy Enhancement for Laku Pandai Agents at the Central Kalimantan Development Bank, Pangkalan Bun Branch,” identifies three key strategies for improving the marketing of Laku Pandai agents in Pangkalan Bun: opening additional sub-branch offices, strengthening agents’ understanding of products and the use of the Betang Mobile application, and enhancing both direct and digital-based promotional activities to ensure wider dissemination of promotional information and potentially increase new account openings